Implementasi Media Pohon Pintar Dalam Meningkatkan Kemampuan Membilang Anak Didik Raudlatul Athfal - Suprihatin Suprihatin (LPPM Institut Agama Islam Nahdlatul Ulama Kebumen, 2023)
Implementation of Smart Tree Media in Improving Numbering Ability. The background is the low ability to count students in RA. The purpose of this study was to determine the increase in numeracy skills after using smart tree media for students of group B RA Al Fatah 2 Danakerta, Punggelan District, Banjarnegara Regency. The design used is a classroom action research design through two cycle stages, each cycle consisting of planning, implementation, observation, and reflection stages. The data used in this study are 1) individual tasks, to determine students' absorption of learning materials; 2) observation, to observe the activities of students and teachers during learning. The results showed that the smart tree media can improve the ability to count. Cycle I can increase the ability to count in the high category to 5 children or 31.25% from the original only 2 children or 12.5% ​​in the initial study. This shows an increase of 18.75 %. And in the second cycle, the children who succeeded in increasing the ability to count in the high category were 13 children or 81.25% or an increase of 50% compared to the first cycle, so it can be concluded that the smart tree media can improve students' learning outcomes in counting, learning becomes more interesting. , fun and encourage children to be more actively involved.